CREATIVE COMPONENT OF THE PROFESSIONAL ACTIVITY OF A UNIVERSITY TEACHER - Georgiyevna Sergeeva, Marina; Leonidovna Sokolova, Natalia; Lvovna Kunitsyna, Maria; Mikhailovna Rozhnova, Tatiana; Sergeyevna Rozhnova, Ksenia; Vasilyevna Paklina, Anna; Alexandrovna Berseneva, Marina (Revista Inclusiones, 2019)
The creative potential of a teacher’s personality has a huge impact on high-quality specialist training, implementing the strategic line of teaching creativity with creativity when shaping the student’s readiness for constant search in informational and educational space. The body of knowledge and the requirements for it do not determine the essence of the teaching profession. A particular feature of this profession is that it has an impact on the entire lifestyle of the teacher in terms of its regime, working conditions, format and didactic form of communication with students, as well as emotional and volitional load. Moreover, teaching activities are more personality-centered than other professions and, therefore, personal qualities of the teacher play a significant role in achieving professional success. Pedagogical work is and will be creative because students, circumstances and the personality of the teacher are unique; thus, any pedagogical decision should come from these constant nonstandard factors. A teacher can only educate the way they wereveducated and do it as long as they work on their development, education and improvement of their pedagogical excellence. Pedagogical activity is one of the most difficult areas of human labor. Even the most profound knowledge of the subject is not enough for the successful performance of work. The work of a teacher is not a craft, but an art that requires from them great knowledge, high culture and pedagogical excellence